Епістолярний діалог Г. Кочура та І. Воронович: сімейний портрет в інтер’єрі «червоної доби» - Колошук, Надія Георгіївна; Koloshuk, Nadiia G. (My University, 2019)
Мова йде про один з епістолярних діалогів середини минулого століття, опублікований до 110-ліття геніального перекладача Г. Кочура. Епістолярна історія кочурівської родини промовиста тим, що показує стосунки найближчих людей із багатьма умовчаннями (з огляду на перлюстрацію), практично не містить відгуку на соціальні й політичні події. Увесь текст родинного листування, за винятком переписаних у листах поетичних перекладів Кочура, має переважно побутовий характер і відповідну стилістику. Однак це й діалог Поета з його Музою. У ситуації нищівної русифікації, коли все українське опинилася на грані незворотного процесу зникнення, перекладацька праця стала авангардною сферою творчості й водночас останнім редутом опору, де митці відчували себе покликаними боронити гідність рідної культури. Ця ситуація спонукала Г. Кочура після табору свідомо вибрати для себе перекладацьку працю, до якої мав унікальний хист і знання, хоча й не мав ні сприятливих умов, ні офіційної підтримки.
The epistolary dialogue of G. Kochur and I. Voronovich: a family portrait in the interior of the "Red Era"
This is one of the epistolary dialogues of the middle of the last century, published before the 110th anniversary of the brilliant translator G. Kochur. The epistolary story of the Kochur’s family is clear by showing the relationship of the closest people with many defaults (taking into account the interception of their letters). It has virtually no response to social and political events. The entire text of the family correspondence, with the exception of those rewritten in the letters of poetry translations of Kochur, has a predominantly everyday character and corresponding stylistics. However, this is the dialogue between the Poet and his Muse. In a situation of crushing Russification, when all Ukrainian was on the verge of an irreversible process of disappearance, the translation work became the avant-garde sphere of creativity and at the same time the last redoubt of resistance, where the artists felt they were called to defend the dignity of their native culture. This situation prompted G. Kochur after the concentration camp to deliberately choose a translation work for himself, to which he possessed a unique skill and knowledge, although he did not have either favorable conditions or official support.
Keywords: Григорій Кочур; Ірина Воронович; епістолярій; родинні листи; переклад; становище колоніальної культури; неофіційний дискурс; побутова тематика; Grigory Kochur; Irina Voronovich; epistolary; family letters; translation; position of colonial culture; informal discourse; household themes